Contrast Ratios, Colour Elements, and Polarities in Visual Acuity Measurements - Hong Chen, Ai; Muhamad, Nurulain (International Journal of Engineering and Technology, 2018)
This study was aimed to investigate the effects of contrast ratios, colour elements, and polarities on visual acuity measurements. The visual acuities of 18 subjects were measured using 6 different modifications of the Landolt C chart in a 4-metre LogMAR design: (M1) black-on-white [contrast ratio: 0.8]; (M2) white-on-black [contrast ratio: 0.8]; (M3) black-on-white [contrast ratio: 0.5]; (M4) yellow-on-green [contrast ratio: 0.8]; (M5) yellow-on-green [contrast ratio: 0.5]; and (M6) black-on-yellow [contrast ratio: 0.8]. Comparative analysis was performed to examine the effects of the three aforementioned parameters on visual acuity measurements. The visual acuities were found to be significantly different between the contrast ratios of 0.5 and 0.8, regardless of whether colour elements were present (black-on-white) or otherwise (yellow-on-green) [Friedman test: c2 (3) = 24.24, p < 0.05]. Interestingly, the LogMAR score was found to be significantly different between the yellow-on-green and black-on-yellow chart designs when the contrast ratio remained constant at 0.8 [Wilcoxon signed-rank test: z = 2.950, p < 0.05]. However, the effect of contrast polarity (positive/ negative) on visual acuity was not significant when the contrast ratio was fixed at 0.8 [Wilcoxon signed-rank test: z = 0.318, p > 0.05].Â A lower contrast ratio and mid-range wavelength colour reduced visual acuity. The effect of contrast polarity without colour elements on visual acuity was negligible.Â Â